Kinerja Pegawai Di Kantor Desa Lombonga Kecamatan Balaesang Kabupaten Donggala - Filo Leonardo Tinggogoy; Fachrul Reza (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan-Palu, 2022)
Employee performance is the extent to which the employee can carry out the task well in the sense that the implementation is in accordance with the plan, so that satisfactory results are obtained for achieving good employee performance. So employees are required to have quality human resources who are able to carry out their duties as government officials in accordance with the tasks assigned. The purpose of this study was to find out how the performance of employees in Lombonga Village, Balaesang District, Donggala Regency. The informants in this study were the office staff of Lombonga Village. the informants are the Village Head, Village Secretary, Employees, Community. The results showed that to determine the performance and sincerity of employees in carrying out their duties and functions at the Lombonga Village office, Balaesang District, Donggala Regency. The author chooses the theory that is considered more suitable to be applied to government organizations, in this case Lombonga Village, Balaesang District, Donggala Regency, is Kumorotomo's theory in Agus Dwiyanto, (2008:52) namely: Efficiency, Effectiveness, Justice, Responsiveness. So it can be concluded that the performance of employees is quite good in its implementation. The influencing factors are the ability of human resources and the state of facilities and infrastructure which are important aspects for the creation of quality work.